Trópicos de lágrimas : um estudo sobre melodrama e América Latina a partir do cinema de cabaretera mexicano e da literatura de Manuel Puig - Bragança, Maurício de (2007)
8 Since its modern origins were linked to the manifestations of the popular classes at the end of the eighteenth century in Europe, through the repertoire of theatrical representation and that of pantomime, melodrama would come to be seen as a genre of ill repute, viewed with suspicion by an erudite elite. In the construction of its discourse, melodrama relied upon an aesthetic of exaggeration, whereby overstated feeling was at the service of the configuration of a melodramatic pathos, forming a narrow syntony with what Peter Brooks defined as a melodramatic imagination . In Latin America, melodrama transformed itself into an idiom present in multiple experiences of the cultural industry. In Mexico, it gave rise to a media circuit formed by cinema, radio, mass literature, and the popular song. In the formation of the national state after the Revolution of 1910, melodrama represented a powerful ally, capable of intoning the discourses constructed in relation to the popular national identity of the day with the new codes of Mexicanness proposed by the populist state. This tradition represented by melodrama in the continent would come to be reappropriated from new points of interpretation, forged in the perspective of the nineteensixties. In this sense, the arrival of Manuel Puig to the Hispano-American literary field at the end of that decade, brought debates that shook the influential models of a literary taste for a certain part of the Argentinean critical circle. Using the resources of idioms and the repertoire present in the cinematographic melodramas and in the feuilleton literature, Manuel Puig relocated the discussions about a cultural colonialism present in the relation centre and periphery, in new fields. This thesis locates melodrama as a catalysing space of a universe of values in which the political and social discussions that compose the cultural spectrum of the two Hispano-American historical contexts are present. In a comparative reading, we discuss melodrama from the basis of a repertoire of Mexican films of the second half of the decade of the forties, known as cine de cabareteras and the literature of Manuel Puig, in particular his debut novel La traición de Rita Hayworth, published in 1968. To theoretically sustain our analyses, we use an approach based upon literary theory, the theories that tackle media processes and historical perspectives that permit us to trace an interdisciplinary mode of thought for a wide approach to cultural studies in Latin America.